2011
DOI: 10.1016/j.enpol.2010.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Understanding public responses to offshore wind power

Abstract: a b s t r a c tThis paper is about understanding the role and importance of public responses to offshore wind power. It builds on a framework for understanding social acceptance and opposition to onshore turbines, and reviews the emerging research on offshore wind. While less is known about how people will respond to offshore than onshore wind, there is now an emerging body of research. From this literature, several common factors which influence responses have emerged and are discussed here: the (continued) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
141
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(149 citation statements)
references
References 47 publications
4
141
0
1
Order By: Relevance
“…In recent years a body of work exploring the relevance of the concept for explaining opposition specifically to RETs has developed (Bell et al 2005;Kempton et al 2005;Wolsink 2000;2012;Haggett 2010;Devine-Wright 2011;Van der Horst 2007). In common with the wider literature, there is an emerging consensus that NIMBYism is an inaccurate and unhelpful way of characterizing opposition to siting.…”
mentioning
confidence: 99%
“…In recent years a body of work exploring the relevance of the concept for explaining opposition specifically to RETs has developed (Bell et al 2005;Kempton et al 2005;Wolsink 2000;2012;Haggett 2010;Devine-Wright 2011;Van der Horst 2007). In common with the wider literature, there is an emerging consensus that NIMBYism is an inaccurate and unhelpful way of characterizing opposition to siting.…”
mentioning
confidence: 99%
“…This is especially the case where local communities are likely to feel powerless about the implementation of the technology in their locality [61]. It is also suggested that the public should be included in decision-making with both on-and off-shore developments [71].…”
Section: Social Issuesmentioning
confidence: 99%
“…It is also suggested, for the impact of offshore wind, that the level of resistance will be determined by how frequently individuals use beaches and for what type of activity (and therefore how likely they are to see and come into contact with developments) [70]. Level of place attachment and relationships with developers and outsiders have also been noted as key factors affecting acceptance [71][72][73]. These issues are also likely to be of relevance to any seaweed farming aspects.…”
Section: Social Issuesmentioning
confidence: 99%
“…Social barriers were generally not experienced in this case study due to an accepting public and sparsely populated rural environment. Despite this Haggett (2011) describes how widespread public resistance, associated planning difficulties and lengthy delays with windfarm development may be attributed to the consequential social disturbances in the form of visual, noise, harm to birdlife, local ecology and environment. Political barriers point towards the consideration and im plem entation of wind energy initiatives within public policy.…”
Section: W Ind Energy Fundam Entalsmentioning
confidence: 99%